2023
DOI: 10.3390/jcm12041367
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences, Motor Skills and Physical Fitness Heterogeneity in Adults with Down’s Syndrome

Abstract: Background—Adults with Down’s syndrome (DS) present lower physical fitness associated with heightened sedentary behaviors and motor skills impairments. Their etiologies and determinants seem to be heterogeneous. This study aims to evaluate physical fitness in adults with DS and to identify specific physical fitness profiles depending on gender and physical activity levels. Methods—Forty adults with DS (16 women, 24 men, 29.7 ± 7.5 years) performed six tests from the EUROFIT Battery and Motor Assessment Battery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 61 publications
(90 reference statements)
0
0
0
Order By: Relevance
“…fasted, caffeine, alcohol and exercise abstention prior to measurements; Data S2). Only three studies reported that examiners had previous experience with the population and testing (Wee et al 2015;Ayán-Pérez et al 2017;Covain et al 2023), and 10 protocols reported standardisation of the environment with regard to temperature and/or humidity (Pitetti et al 1992;Pitetti & Boneh 1995;Tsimaras et al 2003;Mendonca et al 2010;Mendonca et al 2010b;Mendonca et al 2011a,b;Boer & Moss 2016a,b;Oviedo et al 2021).…”
Section: Standardisation Of Exercise Protocolsmentioning
confidence: 99%
See 3 more Smart Citations
“…fasted, caffeine, alcohol and exercise abstention prior to measurements; Data S2). Only three studies reported that examiners had previous experience with the population and testing (Wee et al 2015;Ayán-Pérez et al 2017;Covain et al 2023), and 10 protocols reported standardisation of the environment with regard to temperature and/or humidity (Pitetti et al 1992;Pitetti & Boneh 1995;Tsimaras et al 2003;Mendonca et al 2010;Mendonca et al 2010b;Mendonca et al 2011a,b;Boer & Moss 2016a,b;Oviedo et al 2021).…”
Section: Standardisation Of Exercise Protocolsmentioning
confidence: 99%
“…With regard to BMI, only three studies out of the 43 included participants with DS whose mean BMIs fell within the normal range (20-24.9) (Bricout et al 2008;Leti et al 2015;Covain et al 2023). The mean BMI of the study samples was between 25 and 29.9 (overweight) in 17 studies and between 30 and 34.9 (obesity class I) in 14 studies.…”
Section: Sample Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Children with Down syndrome have neuromuscular disorders that cause developmental delays, poor movement quality, and poor balance [10]. Movement difficulties linked with Down syndrome can lead to a more sedentary lifestyle and decreased physical fitness, with adults having poorer aerobic capacity than healthy people [11,12]. In addition, children with Down syndrome consistently show decreased upper and lower body muscle strength compared to children with normal conditions [13].…”
mentioning
confidence: 99%